2001
DOI: 10.1128/jcm.39.11.4111-4118.2001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Examination of Human Intestinal Spirochetosis by Fluorescent In Situ Hybridization for Brachyspira aalborgi , Brachyspira pilosicoli , and Other Species of the Genus Brachyspira ( Serpulina )

Abstract: Human intestinal spirochetosis, characterized by end-on attachment of densely packed spirochetes to the epithelial surface of the large intestines as a fringe has been associated with the weakly beta-hemolytic spirochetes Brachyspira aalborgi and Brachyspira (Serpulina) pilosicoli. In this study, fluorescent in situ hybridization with oligonucleotide probes targeting 16S or 23S rRNA of B. aalborgi, B. pilosicoli, and the genus Brachyspira was applied to 40 sections of formalin-fixed, paraffin-embedded intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 42 publications
4
60
0
1
Order By: Relevance
“…This is the first study to provide an estimate of the prevalence of B. aalborgi in the general population of a developing country. Unfortunately, there have been no studies on the prevalence of B. aalborgi in developed countries, apart from in selected groups of patients who have undergone colorectal biopsy for underlying complaints of the large bowel [21,[25][26][27][28]. In the absence of this comparative data, it is not possible to determine whether the prevalence of colonization that was detected is unusually high or low, or whether it was influenced by factors peculiar to developing countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first study to provide an estimate of the prevalence of B. aalborgi in the general population of a developing country. Unfortunately, there have been no studies on the prevalence of B. aalborgi in developed countries, apart from in selected groups of patients who have undergone colorectal biopsy for underlying complaints of the large bowel [21,[25][26][27][28]. In the absence of this comparative data, it is not possible to determine whether the prevalence of colonization that was detected is unusually high or low, or whether it was influenced by factors peculiar to developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…To date, B. aalborgi has only been reported to have been isolated from humans in five studies; in three it was grown from colorectal biopsies [1,21,22], and in two it was grown from faeces [23,24]. In recent studies, DNA has been extracted from colorectal biopsies taken from IS patients in Australia, Scandinavia and the United States, and amplified by polymerase chain reaction (PCR) or hybridized with oligonucleotide probes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. aalborgi is difficult to culture due to its fastidious growth requirements and extremely slow growth rate. It is usually detected by polymerase chain reaction (PCR) or gene probe assays, and has only occasionally been isolated [5][6][7]. B. pilosicoli is easier to isolate, and has been cultured from faeces in several developing countries [8][9][10][11], from Australian Aborigines [12,13], migrants to Australia from developing countries [13] and homosexual males [14].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that HIS is associated with various intestinal diseases, including colon carcinoma and colonic polyps (9,10). Previous reports (9, 10) have also shown that HIS can be found in cases of ulcerative colitis.…”
Section: Introductionmentioning
confidence: 98%